Schematic Structure of Kandatu Speeches: A Genre-Based Analysis: Struktur Skematis Pidato Kandatu: Analisis Berbasis Genre - Sittie Aina T. Pandapatan; Basmah S. Hussain; Alican Pandapatan (SiRad: Pelita Wawasan, 2026)
The study aimed to analyze the schematic structure of Kandatu speech of Meranaw and to develop a model genre structure. The study employed a qualitative research design specifically descriptive. The data were collected from the three kandatu speeches. The study identified the obligatory moves in the public speeches. Without these obligatory moves, the speech will not be complete as a specific genre. Using the genre-based analysis of Swales (1990), the researcher identified the schematic structure of Kandatu speech. With the Huttner’s (2010) framework of classifying moves and steps, the study identified 10 obligatory steps for the three obligatory moves. For the Move 1 (Introduction), the obligatory steps were Basmalah, Greeting, Praising Allah, and Praising Muhammad. For the Move 2 (Body), the identified obligatory steps were Describing the ceremony, Stating the purpose of the ceremony, Narrating historical/religious accounts, and Discussing the importance of insana (trust). For the Move 3 (Conclusion), the obligatory steps were seeking consensus from the respected datus and greeting. Future researchers may focus also on the other Meranaw speeches to test genre relative to the Kandatu speeches. This would support strongly the genre being established and analyzed. [Penelitian ini bertujuan untuk analisis struktur skematis pidato Kandatu masyarakat Meranaw serta mengembangkan suatu model struktur genre. Penelitian ini menggunakan desain penelitian kualitatif, khususnya bersifat deskriptif. Data dikumpulkan dari tiga pidato Kandatu. Penelitian ini mengidentifikasi langkah-langkah (moves) wajib dalam pidato publik tersebut. Tanpa adanya langkah-langkah wajib ini, pidato tidak dapat dianggap lengkap sebagai suatu genre tertentu. Dengan menggunakan analisis berbasis genre dari Swales (1990), peneliti mengidentifikasi struktur skematis pidato Kandatu. Selanjutnya, dengan menggunakan kerangka klasifikasi langkah dan tahapan dari Huttner (2010), penelitian ini mengidentifikasi sepuluh tahapan wajib yang termasuk dalam tiga langkah wajib. Pada Langkah 1 (Pendahuluan), tahapan wajib yang ditemukan meliputi pembacaan Basmalah, salam pembuka, pujian kepada Allah, dan pujian kepada Nabi Muhammad. Pada Langkah 2 (Isi), tahapan wajib yang diidentifikasi meliputi deskripsi upacara, penyampaian tujuan upacara, penceritaan kisah-kisah historis atau keagamaan, serta pembahasan mengenai pentingnya insana (kepercayaan). Pada Langkah 3 (Penutup), tahapan wajib meliputi permohonan kesepakatan dari para datu yang dihormati dan penyampaian salam penutup. Para peneliti di masa mendatang, mari memfokuskan perhatian pada pidato Meranaw lainnya untuk menguji genre relatif terhadap dialek Kandatu. Hal ini akan sangat mendukung genre yang sedang ditetapkan dan dianalisis.]